2017
DOI: 10.1080/21681376.2017.1412270
|View full text |Cite
|
Sign up to set email alerts
|

A childless urban renaissance? Age-selective patterns of population change in North American and German Metropolitan areas

Abstract: INTRODUCTION 'Do cities need kids?'-in the February 2015 issue of Governing Magazine, Alan Greenblatt used this provocative title for his article on gentrification in Seattle, Washington. According to him, Seattle is 'not necessarily a place that is welcoming to families' (Greenblatt, 2015, p. 1). The population of downtown Seattle has grown significantly in recent years, and families have indeed taken ABSTRACT Since the 1980s and 1990s, many metropolitan areas in north america and europe have registered popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 49 publications
0
13
0
2
Order By: Relevance
“…These areas are very likely to be in the focus of current and next year's reurbanisation as they may become attractive for families. This issue is, however, contradictorily discussed in the current reurbanisation debate (Lilius, 2014;Siedentop, Zakrzewski, & Stroms, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…These areas are very likely to be in the focus of current and next year's reurbanisation as they may become attractive for families. This issue is, however, contradictorily discussed in the current reurbanisation debate (Lilius, 2014;Siedentop, Zakrzewski, & Stroms, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…As has been shown above, the demographic change plays a major role in East Germany's shrinking cities and the patterns of population development vary strongly with regard to different demographic groups. In addition, Siedentop, Zakrzewski, and Stroms (2018) have shown that recent tendencies of reurbanization in Germany are largely driven by the inflow of young adults. The factors steering the migration behavior and urban population development may, therefore, strongly vary across different personal lifecycle stages (see e.g., Chen & Rosenthal, 2008;Ferguson et al, 2007;Graves, 1979).…”
Section: Estimation Strategymentioning
confidence: 99%
“…Within these metropolitan areas, housing is being added in the centers through infill and at the suburban fringes. Particularly in the global North, demographic changes have contributed to a growth in smaller households, which has fueled the redevelopment of the urban cores of cities, often in the form of high-rises (Siedentop, Zakrzewski & Stroms, 2018). However, most new housing, whatever form it takes in different contexts, such as single-detached or high-rises, is indeed suburban (Keil, 2017).…”
Section: Demographic Changesmentioning
confidence: 99%